2020
DOI: 10.31838/jcr.07.05.18
|View full text |Cite
|
Sign up to set email alerts
|

Profiling Disabled Facilities and Accessibility Provided in National Heritage Buildings in Malaysia

Abstract: The national heritage buildings in Malaysia have gained popularity due to their various historical upbringing and culture. They attract both local and international tourists. However, lack of facilities for the disabled people has hindered their prospects to become globally popular. The purpose of this research is to determine the extent of disabled facilities and accessibility in the national heritage buildings. This research opted for qualitative methods to achieve its purpose. Three case studies were select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
0
0
Order By: Relevance
“…Ismail et al (2015), who highlighted on the low level of concerns by the community and administration in relation to this issue. According to Kamaruddin et al (2012) and Zahari et al (2020), the main reasons why people with disabilities are unable to participate in social activities inadequate accessibility features, especially in public spaces. They believed that the PwDs are being ignored and prevented from participating in society.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Ismail et al (2015), who highlighted on the low level of concerns by the community and administration in relation to this issue. According to Kamaruddin et al (2012) and Zahari et al (2020), the main reasons why people with disabilities are unable to participate in social activities inadequate accessibility features, especially in public spaces. They believed that the PwDs are being ignored and prevented from participating in society.…”
Section: Discussion Of Findingsmentioning
confidence: 99%
“…Ismail et al (2021) mentioned that students with physical and sensory impairments face great challenges and obstacles in higher education, which have impaired their capacity to study. Zahari et al (2020) also argued that the current conservation guidelines and requirements are not comprehensive enough to address the disabled facilities and accessibility aspects. They are not being highlighted as important criteria in conserving heritage buildings.…”
Section: Pwds and Accessibility Issuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, future research should also explore research related to facilities that can help disabled employees to perform their jobs better. For example, Zahari et al (2020) found that facilities that are prepared for disabled persons in heritage buildings in Malaysia are insufficient, causing barriers for disabled persons to enter those buildings. The research implicitly revealed that not only heritage buildings but many buildings for working organisations also did not provide sufficient facilities for disabled employees to support high job performance.…”
Section: Research Significancementioning
confidence: 99%